The regulatory effect of alginate on ovalbumin-induced gut microbiota disorders. (November 2021) - Yao, Lijun; Yang, Peng; Lin, Yue; Bi, Decheng; Yu, Boming; Lin, Zhijian; Wu, Yan; Xu, Hong; Hu, Zhangli; Xu, Xu
Graphical abstract: Highlights: Alginate changed the secondary structure of ovalbumin (OVA) through interaction in vitro . Alginate treatment attenuated OVA-induced gut microbiota disorder in mice. This is the first study to investigate the effects of alginate on OVA-induced gut microbiota dysbiosis in mice. Abstract: Alginate is a dietary polysaccharide that exerts antioxidative, immunomodulatory and anti-allergic effects. In this study, the effects of alginate on the secondary structure of ovalbumin (OVA) in vitro and on the regulation of OVA-induced gut microbiota disorders in vivo were investigated. First, the interactions between OVA and alginate were studied by multiple spectroscopic methods, which showed that alginate could change the secondary structure of OVA. Then, the regulation of allergic diarrhoea by alginate was evaluated in OVA-sensitized mice, which demonstrated that alginate could attenuate allergic diarrhoea and duodenal morphological damage. Additionally, when diarrhoea symptoms were ameliorated by alginate, the richness and diversity of the gut microbiota could be partially restored, and the relative abundances of Alloprevotella, Bacteroides, Parabacteroides and Rikenellaceae_RC9_gut_group showed recovery trends. Therefore, alginate could improve OVA-induced gut microbiota disorder, and alginate could be used as a potential agent for intestinal protection in the food or pharmaceutical industry.